What Is Digital Journalism? Defining the Practice and Role of the Digital Journalist. Issue 10 (12th November 2020) - Perreault, Gregory P.; Ferrucci, Patrick
Abstract: Through the lens of theories of field and normalization process, this research seeks to understand technology's current role in how self-identifying digital journalists define the field. The definitions of digital journalism/journalists and what constitutes digital journalism practices are essential–they shape a range of crucial activities including how journalists prioritize sources to how journalists shape their content for audience consumption. Built on long-form interviews with 68 U.S.-based self-identifying digital journalists, this article argues that the digital turn in the industry has emboldened new entrants to the field and required dominantly placed legacy media journalists to reconsider their definition of journalism as well as their practices. Rather than seeing digital journalism as a sub-field within journalism, participants saw digital journalism as business-as-usual throughout the journalistic field.